Production of phenolics by Rhizoctonia bataticola (taub.) Butler during pathogenesis - Tripta Sapru; S.K. Mahajan (Environment Conservation Journal, 2010)
Rhizoctonia bataticola is a facultative parasite, which causes damping of seedlings and root rot in vegetables, cereals, fruits, oilseed crops and ornamental plants. The present paper deals with the in vitro studies of the production of phenolics by this parasitic fungus.